Culture-independent and -dependent methods to investigate the diversity of planktonic bacteria in the northern Bering Sea - Zeng, Yinxin; Zou, Yang; Grebmeier, Jacqueline M.; He, Jianfeng; Zheng, Tianling; 郑天凌 (POLAR BIOL, 2012)
National Natural Science Foundation of China [40676002, 40930847, 31070442, 41076130, 41076131]; Emphasis Project Fund of National Scientific and Technical Support Plan [2006BAB18B07]; International Science and Technology Cooperation Program [2008DFA20420]; U.S. National Science Foundation [NSF-OPP-ARC-0454454]; Public Science and Technology Research Funds Projects of Ocean [201105022] Planktonic bacteria are abundant in the Bering Sea. However, very little is known about their diversity and the roles of various bacteria in the ocean. Bacterioplankton diversity in the northern Bering Sea was investigated using a combination of molecular and cultivation-based methods. Community fingerprint analysis using polymerase chain reaction-denaturing gradient gel electrophoresis revealed an apparent difference in the bacterioplankton community composition between sampling locations in the area. The bacterial communities were characterized by two 16S rRNA gene clone libraries for surface and bottom water at shallow station NEC5 (< 60 m in depth) on the continental shelf. Sequences fell into 21 major lineages of the domain Bacteria, including Proteobacteria (Alpha, Beta, Gamma, and Delta), Bacteroidetes, Actinobacteria, Firmicutes, Acidobacteria, Planctomycetes, Verrucomicrobia, Fusobacteria, Chlamydiae, Chloroflexi, Chlorobi, Spirochaetes, Cyanobacteria (or algal chloroplasts), and candidate divisions OP8, OP11, TM6, TM7, and WS3. Significant differences were found between the two clone libraries. Actinobacteria formed the dominant bacterial lineage in both surface and bottom water, and the Alphaproteobacteria was another dominant fraction in surface water. A total of 232 heterotrophic bacterial strains were isolated and 81% showed extracellular proteolytic activity. Phylogenetic analysis revealed that the isolates fell into three bacterial groups, including the Gammaproteobacteria, Actinobacteria, and Firmicutes. The most common genus in both the bacterial isolates and protease-producing bacteria was Pseudoalteromonas. Divergence of bacterial community composition in the northern Bering Sea was mainly characterized by the dominance of Actinobacteria and reflected a bacterial community different from that currently known for marine bacterioplankton communities in other polar regions.